Family witnessed resuscitation: nationwide survey of 337 prehospital emergency teams in France. Issue 12 (6th December 2012) - Belpomme, Vanessa; Adnet, Frederic; Mazariegos, Ixchel; Beardmore, Matt; Duchateau, François-Xavier; Mantz, Jean; Ricard-Hibon, Agnes
Abstract : Objective: To assess the practices and opinions of prehospital emergency medical services (EMS) with regard to family witnessed resuscitation (FWR) and to analyse the differences between physicians' and nurses' responses. Design: An anonymous questionnaire (30 yes/no questions on demographics and FWR) was sent to all prehospital emergency staff (physicians, nurses and support staff) working for the 377 Mobile Intensive Care Units in France. Results: Of the 2689 responses received 2664 were analysed. Mean respondent age was 38±8 years, the male to female ratio was 1:2. 87% of respondents had already performed FWR and 38% had offered relatives the option to be present during resuscitation. Most respondents (90%) felt that FWR might cause psychological trauma to the family; 70% thought that FWR might impact on the duration of resuscitation and 68% on EMS team concentration. In the 28% of cases when relatives had asked to be present, 59% of respondents had acquiesced but only 27% were willing to invite relatives to be routinely present. Conclusions: Prehospital EMS teams in France seems to support FWR but are not yet ready to offer it systematically to relatives. Following our survey, written guidelines are currently in development in our department. These guidelines could be the first step of a national strategy for developing FWR in France. We await results from other studies of family members' opinions to compare prehospital practitioners' and family members' views to further develop our practice.